Acute transsynaptic regulation of tyrosine 3-monooxygenase activity in the rat superior cervical ganglion: evidence for both cholinergic and noncholinergic mechanisms. - Ip, N Y (1983)
The rate of dopa synthesis in the rat superior cervical ganglion was increased 4- to 6-fold during continuous electrical stimulation of the cervical sympathetic trunk at 10 Hz for 30 min. This increase was only partially blocked by 3 mM hexamethonium and was not significantly affected by 6 microM atropine. In the presence of both hexamethonium and atropine, nerve stimulation still produced a 2- to 4-fold increase in dopa synthesis. Physostigmine increased dopa synthesis in both control and stimulated ganglia. This effect of physostigmine was completely blocked by hexamethonium and atropine. Dopa synthesis was also significantly increased when ganglia were incubated in a medium containing an elevated concentration of K+ (55 mM). This stimulatory effect of high K+ was totally dependent on the presence of Ca2+ in the medium, was decreased by 60% by prior decentralization of the ganglion, and was unaffected by hexamethonium and atropine. The data demonstrate that tyrosine hydroxylase activity is rapidly increased after preganglionic nerve stimulation and suggest that this increase is mediated in part by acetylcholine and in part by a second (noncholinergic) transmitter. The effects of an elevated K+ concentration may be mediated both by the release of a noncholinergic transmitter from the preganglionic nerve terminals and by direct depolarization of the ganglionic neurons.